Compositional analysis of treated wastewater at the Termez city wastewater treatment plant (Международный научный журнал «Инженер», 2026)
Water is the main resource that ensures the continuation of life. Rapid population growth,industrialization, urbanization and widespread agricultural expansion have led to the production ofcontaminated wastewater. Millions of people die every year from diseases caused by drinking watercontaminated with harmful microorganisms. 80% of child deaths and diseases worldwide are associatedwith poor water quality. The environment is seriously threatened by these pollutants. Removing harmfulsubstances from wastewater is a major problem. Traditional treatment methods allow only 30-40%purification of contaminated water. In our research work, samples were taken from a depth of 20 cm fromthe outlet of relatively purified wastewater into an open water body to conduct a chemical analysis ofsewage wastewater from three-stage treatment processes at the Termez city wastewater treatment plantof Surkhandarya Water Supply A/J. The samples were tested in the laboratory of the SurkhandaryaRegional Department of Ecology, Environmental Protection and Climate Change. The results wereanalyzed and compared with the state standards for the discharge of wastewater into open water bodies.